(untitled) (Research, Society and Development, 2021)
Objective: This study aimed to evaluate the relations between orbit-related structures and sex, age and skeletal deformities using cone-beam computed tomography (CBCT). Methods: This retrospective study evaluated 216 consecutive CBCT scans of patients, who were divided according to: sex (male, n=105; female, n=111), age (A1: 18-32 years, n=71; A2: 33-47 years, n=78; A3: 48-62 years, n=67), and skeletal deformities (Class I, n=70; Class II, n=75; Class III, n=71). The supraorbital foramen (SOF) location, volume of orbit, optic canal (OC) and infraorbital canal (IOC) were evaluated. Results were analyzed using the Gamma model test. The Tukey-Kramer post-hoc test was used to compare the variables with three factors (p<0.05). Results: The IOC volume showed higher values for male, A3 and class I patients. The SOF location and the orbital volume also showed higher values for male patients. Regarding the volume of CO, it showed higher values ​​for male and class I patients. Conclusions: According to our results, sex has been shown to have a significant influence on orbit-related structures. Age and skeletal deformities also influenced the volume of IOC and OC. These results eventually help the clinical practice, being useful for orbital reconstruction surgeries, anthropological studies, gender identification and identification of susceptibility to pathological conditions related to sexual dimorphism.